Malnutrition of the oncological patient - diagnosis and prevention - Małgorzata Nartowicz; Aleksandra Jaworska-Czerwińska; Sonia Nartowicz; Magda Kucharczuk (Kazimierz Wielki University, 2018)
Introduction: Malnutrition is an important medical problem which affects more than half of patients at the time of diagnosis of cancer, before any treatment begins. Deficits of nutrients in this group of patients have enormous impact on the course of the disease, tolerance of anti-cancer treatment, quality of life and mortality. Weight loss is observed in 30% to over 80% of patients and depends on the type of cancer, location and its severity. Abnormal nutritional status is also one of the causes of a weaker response to the applied anti-cancer treatment (both local and systemic) and, consequently, probably worse prognosis and shorter survival time, and more frequent occurrence of adverse effects and severe complications of anti-cancer therapy that force premature its completion. Patients with malnutrition occurs increased incidence of infectious complications, which worsens their prognosis. Worse healing of wounds after surgical procedures is observed, patient stays longer in the hospital, and the date of commencement of adjuvant treatment goes away. Cancer cachexia may result in feelings of weakness, fatigue, and increase the risk of depression and aggravate the general condition. The aim of the work is to present the essence of the problem which is malnutrition, especially in oncological patients. Summary: Proper nutrition, adapted to the current clinical situation and covering demand, is still an underestimated element of treatment of patients. Properly conducted nutritional therapy in oncological patients is an important element of treatment, because it creates optimal conditions for recovery and reduces the risk of relapse.